The development and implementation of a mobile announcement system-an analysis of user technology acceptance based on perceived ease of use and perceived usefulness. / Rohaniah Yusof - Yusof, Rohaniah (Faculty of Information Technology and Quantitative Sciences, 2006)
In campus environment, information delivery is one of the most important elements to make lecturers and students become a better information society. Information must be quickly delivered and received by lecturers and students in a timely way. Currently, in the Faculty of Information of Technology and Quantitative Sciences (FTMSK), an ineffective communication approach is still being used to deliver information to students and lecturers. Therefore, Mobile Announcement System (MASY) has been developed and can be considered as a potential approach to achieve this objective. Based on Technology Acceptance Model (TAM) by Davis (1989), data is gathered through a questionnaire which is designed to determine the level of students’ acceptance towards the use of MASY. There are two constructs in the questionnaire, which are Perceived Ease of Use and Perceived Usefulness. The questionnaire contains 15 items based on five-point Likert scale, which are ranging from Strongly Disagree to Strongly Agree. 31 postgraduate students have been involved as respondents. The overall results of this study indicated that students agreed toward the use of MASY because of the effectiveness of its usage (mean=3.74). The mean score for first construct (Perceived Ease of Use) is 3.76 and second construct (Perceived Usefulness) is 3.71. In conclusion, this system has a great potential to enable communication between office-based lecturers and mobile students.